2020
DOI: 10.1002/jbm.b.34570
|View full text |Cite
|
Sign up to set email alerts
|

Collagen‐I/silk‐fibroin biocomposite exhibits microscalar confinement of cells and induces anisotropic morphology and migration of embedded fibroblasts

Abstract: Microstructural anisotropy of tumor-associated matrix correlates with invasion of cancer cells into the surrounding matrix during metastasis. Here, we report the fabrication and characterization of a three-dimensional (3D) silk-fibroin/collagen-I biocomposite based cell-culture model that exhibits microstructural and biochemical anisotropy. Using RGD-deficient silk-fibroin fibers to confine collagen-I gelation, we develop a silk-fibroin/collagen-I (SFC) bio-composite in a one-step process allowing control over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The degree is measured between 0 and 1, where 0 corresponds to a fully isotropic structure, while 1 corresponds to a completely anisotropic structure [ 62 ]. The organization presented by ECM fibers within fabrics can vary from anisotropic (fiber alignment, directional amplification of binder density) to isotropic (randomly aligned, uniform binder availability) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degree is measured between 0 and 1, where 0 corresponds to a fully isotropic structure, while 1 corresponds to a completely anisotropic structure [ 62 ]. The organization presented by ECM fibers within fabrics can vary from anisotropic (fiber alignment, directional amplification of binder density) to isotropic (randomly aligned, uniform binder availability) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts have been previously reported to align in anisotropic conditions. [43,44] Efficient cell adhesion and proliferation has been reported in a collagen/PEG hydrogel using human fibroblasts. [45] Similarly, our results demonstrated that NHDF cells efficiently grew within collagen-Anisogels, exhibiting alignment with the unidirectional orientation of the PEG microgels established during the initial gelation process and up to 7 days in culture.…”
Section: Normal Human Dermal Fibroblasts Cell Behavior In Collagen-an...mentioning
confidence: 99%
“…Compared to the round shape, a spindle-like morphology endows cells with greater migration capability. 26,27 Thus, the alteration in cellular morphology induced by NPs was closely related to the attenuated cell migration.…”
Section: Nps Attenuate Cell Migration Via Altering Cell Morphology An...mentioning
confidence: 99%